Unity, leadership change and vision - Dyer, Kevin G. (Prospect Heights, IL Dr Kevin G. Dyer)
Compilation of four messages given by Dr Kevin G. Dyer at conferences for church leaders.
Contents : Father make us one -- Organising leadership for effective ministry -- The agony of change, the ecstacy of revival -- Vision.
Brethren writer.
Keywords: Brethren movement -- practices